The Function of Myostatin in Ameliorating Bone Metabolism Abnormalities in Individuals with Type 2 Diabetes Mellitus by Exercise - Chenghao Zhong; Xinyu Zeng; Xiaoyan Yi; Yuxin Yang; Jianbo Hu; Rongbin Yin; Xianghe Chen (Current Issues in Molecular Biology)
Purpose: The molecular mechanisms involved in bone metabolism abnormalities in individuals with type 2 diabetes mellitus (T2DM) are a prominent area of investigation within the life sciences field. Myostatin (MSTN), a member of the TGF-β superfamily, serves as a critical negative regulator of skeletal muscle growth and bone metabolism. Current research on the exercise-mediated regulation of MSTN expression predominantly focuses on its role in skeletal muscle. However, due to the intricate and multifaceted mechanical and biochemical interactions between muscle and bone, the precise mechanisms by which exercise modulates MSTN to enhance bone metabolic disorders in T2DM necessitate additional exploration. The objective of this review is to systematically synthesize and evaluate the role of MSTN in the development of bone metabolism disorders associated with T2DM and elucidate the underlying mechanisms influenced by exercise interventions, aiming to offer novel insights and theoretical recommendations for enhancing bone health through physical activity. Methods: Relevant articles in Chinese and English up to July 2024 were selected using specific search terms and databases (PubMed, CNKI, Web of Science); 147 studies were finally included after evaluation, and the reference lists were checked for other relevant research. Results: Myostatin’s heightened expression in the bone and skeletal muscle of individuals with T2DM can impede various pathways, such as PI3K/AKT/mTOR and Wnt/β-catenin, hindering osteoblast differentiation and bone mineralization. Additionally, it can stimulate osteoclast differentiation and bone resorption capacity by facilitating Smad2-dependent NFATc1 nuclear translocation and PI3K/AKT/AP-1-mediated pro-inflammatory factor expression pathways, thereby contributing to bone metabolism disorders. Physical exercise plays a crucial role in ameliorating bone metabolism abnormalities in individuals with T2DM. Exercise can activate pathways like Wnt/GSK-3β/β-catenin, thereby suppressing myostatin and downstream Smads, CCL20/CCR6, and Nox4 target gene expression, fostering bone formation, inhibiting bone resorption, and enhancing bone metabolism in T2DM. Conclusion: In the context of T2DM, MSTN has been shown to exacerbate bone metabolic disorders by inhibiting the differentiation of osteoblasts and the process of bone mineralization while simultaneously promoting the differentiation and activity of osteoclasts. Exercise interventions have demonstrated efficacy in downregulating MSTN expression, disrupting its downstream signaling pathways, and enhancing bone metabolism.